Anthropology of kinship meets human rights rationality: limits of marriage and family life in the European Court of Human Rights - Linda Hart (Taylor and Francis, 2022)
The question of what kinds of constellations of personal relationships are recognised as family life by Member States of the Council of Europe has been under intense litigation in recent years in the European Court of Human Rights (ECtHR). This article examines the ECtHR as an arena where different realms of knowledge come together and produce interpretations of human rights norms according to historically contingent and sometimes conflicting attempts to produce decisions that reflect ‘human rights rationality’. By analysing five judgments from the 2000s and 2010s, this article focuses on State-argued cultural understandings of limits of acceptable forms of marriage and family life. The cases concern marriage between former in-laws, sexual relations between genetically related siblings and understandings of maternity in contexts of egg donation and surrogacy. The judgments offer examples of legal arguments and extra-legal knowledge that have been applied by States and the ECtHR itself when arguing for, or against, giving particular understandings of family life legal protection in interpreting the European Convention on Human.